Integrated biovalorization of wine and olive mill by-products to produce enzymes of industrial interest and soil amendments - Reina, Rocio; Ullrich, René; García-Romera, Inmaculada; Liers, Christiane; Aranda, Elisabet (Spanish Journal of Agricultural Research, 2016)
An integral and affordable strategy for the simultaneous production of lignin-modifying and carbohydrate active enzymes and organic amendment, with the aid of a saprobe fungus was developed by using olive oil and wine extraction by-products. The polyporal fungus Trametes versicolor was cultivated in soy or barley media supplemented with dry olive mill residue (DOR) as well as with grape pomace and stalks (GPS) in solid state fermentation (SSF). This strategy led to a 4-fold increase in the activity of laccase, the principal enzyme produced by SFF, in DOR-soy media as compared to controls. T. versicolor managed to secrete lignin-modifying enzymes in GPS, although no stimulative effect was observed. GPS-barley media turned out to be the appropriate medium to elicit most of the carbohydrate active enzymes. The reuse of exhausted solid by-products as amendments after fermentation was also investigated. The water soluble compound polymerization profile of fermented residues was found to correlate with the effect of phytotoxic depletion. The incubation of DOR and GPS with T. versicolor not only reduced its phytotoxicity but also stimulated the plant growth. This study provides a basis for understanding the stimulation and repression of two groups of enzymes of industrial interest in the presence of different carbon and nitrogen sources from by-products, possible enzyme recovery and the final reuse as soil amendments.